by the rules of powers
(a^m)(a^n) = a^(m+n)
so suppose we multiply
a^m by a^0
by the above law,
a^m(a^0) = a^m
so we multiplied a^m by some value and we got back a^m, no change in value!
the only way this could have happened is that a^0 must have had a value of 1
Suppose you didn't know that b^0=1. Explain how you could arrive at this fact by using the laws of exponents to simplify b^2 times b^0=b^2
I am so confused
Please help me!!
Thanks
~aShLeY
3 answers
okay, that makes sense, thanks so much
what is the value of the expression blow if a=4 and b=-4